2014
DOI: 10.1590/1678-457x.6393
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic compounds and antioxidant activity of hydroalcoholic extracts of wild and cultivated murtilla (Ugni molinae Turcz.)

Abstract: Over the last decade a considerable increase in the number of studies addressing the use of antioxidants from natural sources has led to the identification and understanding of the potential mechanisms of biologically active components. This results from the fact that they can be used to replace synthetic antioxidants commonly used in food. Murtilla (Ugni molinae Turcz) is a native berry grown in Chile, and in the present study, the phenolic composition and antioxidant activity of its fruits were studied. Hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 38 publications
4
39
2
1
Order By: Relevance
“…Acetone is capable to provide high antioxidant activity due to its hydrogen-bonding ability, which is crucial for the extraction of antioxidant phenolic compounds (Rodríguez-Rojo et al, 2012). The efficiency of methanol was related to its intermediate polarity, which allows it to solvate low molecular weight organics compounds possessing protonatable functional groups such as CDDH and DH (Augusto et al, 2014;Nguyen et al, 2015). These functional groups were strongly responsible for a good antioxidant activity.…”
Section: Effect Of Extracting Solvent On the Antioxidant Activitiesmentioning
confidence: 99%
“…Acetone is capable to provide high antioxidant activity due to its hydrogen-bonding ability, which is crucial for the extraction of antioxidant phenolic compounds (Rodríguez-Rojo et al, 2012). The efficiency of methanol was related to its intermediate polarity, which allows it to solvate low molecular weight organics compounds possessing protonatable functional groups such as CDDH and DH (Augusto et al, 2014;Nguyen et al, 2015). These functional groups were strongly responsible for a good antioxidant activity.…”
Section: Effect Of Extracting Solvent On the Antioxidant Activitiesmentioning
confidence: 99%
“…Phenolic compounds (PCs) have been extensively studied due to their antioxidant properties and strong influence on the food quality (Augusto et al, 2014). These compounds include a wide variety of molecules, like phenolic acids, the simplest ones, consisting in a C6-C1 or C6-C3 structure, the flavonoids, which are the most abundant and presenting a C6-C3-C6 structure, and the stilbenes with their C6-C2-C6 structure.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, ethanol and ethanol-water fractions were found to be the most effective in producing scavenging activity against DPPH radicals, and for garden-violet cultivar the highest values were obtained. Several studies showed also that cultivated plants possessed a higher free-radical scavenging activity against DPPH radicals than wild growing plant [17][18][19].…”
Section: Resultsmentioning
confidence: 99%